Accelerating the Worldwide Adoption of Sugar-Sweetened Beverage Taxes: Strengthening Commitment and Capacity; Comment on "The Untapped Power of Soda Taxes: Incentivizing Consumers, Generating Revenue, and Altering Corporate Behavior" - Phillip Baker; Alexandra Jones; Anne Marie Thow (Kerman University of Medical Sciences, 2018)
In their recent article Roache and Gostin outline why governments and public health advocates should embrace soda taxes. The evidence is strong and continues to grow: such taxes can change consumer behavior, generate significant revenue and incentivize product reformulation. In essence, such taxes are an important and now well-established instrument of fiscal and public health policy. In this commentary we expand on their arguments by considering how the worldwide adoption of such taxes might be further accelerated. First, we identify where in the world taxes have been implemented to date and where the untapped potential remains greatest. Second, drawing upon recent case study research on country experiences we describe several conditions under which governments may be more likely to make taxation a political priority in the future. Third, we consider how to help strengthen the technical and legal capacities of governments to design and effectively administer taxes, with emphasis on low- and middle-income countries. We expect the findings to be most useful to public health advocates and policy-makers seeking to promote healthier diets and good nutrition.